Does the speed of the treadmill influence the training effect in people learning to walk after stroke? A double-blind randomized controlled trial. (March 2015) - Lee, In-Hee
Objective: To compare the effectiveness of high-speed treadmill training and progressive treadmill training for stroke patients. Design: A double-blind, randomized controlled trial. Setting: Inpatient rehabilitation hospital. Participants: A total of 61 ambulatory stroke patients. Interventions: Patients in both groups underwent treadmill training for 30 minutes with conventional intervention. The progressive training group ( n = 31) was trained to walk on a treadmill with a stepwise increase of speed over the treatment period. The high-speed training group ( n = 30) trained to begin at 1.2–1.3 m/s, which is faster than the mean speed of stroke patients. All participants underwent 20 training sessions for five weeks. Main measures: Timed up-and-go test, 10-m walk test, 6-minute walk test, and both step lengths and cadence. Results: There were significant improvements in the results of the timed up-and-go test (−1.96 vs. −5.02 seconds), 10-m walk test (0.30 vs. 0.47 m/s), 6-minute walk test (38.35 vs. 64.40 m), and in the step length of the affected side (0.14 vs. 0.19 m) and the unaffected side (0.10 vs. 0.12 m) in the high-speed training group compared with those in the progressive training group ( p < 0.05). Step width was not changed in either group ( p > 0.05). Conclusion: These results suggest that high-speed training is an effective method for improving the walking ability of stroke patients.